Effect of Mahjong on children's intelligence quotient - Higashijima, Takefumi; Akimoto, Taisuke; Sakata, Katsumi (Frontiers in Psychology, 2022)
This study investigated the effect of Mahjong, which is a table game played by three or four players and involves intellectual activity, on the intelligence quotient (IQ) of children. The participants were children between the age of 6 and 15 years, and their IQ was assessed immediately after enrolling in children's Mahjong classes and 1 year after the enrollment using the Wechsler Intelligence Scale for Children Fourth Edition (WISC-IV). Twenty children were included in the analysis. Their mean age at the time of the initial evaluation was 9 years and 6 months. In addition, we conducted a 1-year post-examination. The change in the IQ of this group was compared to that of a historical control group with a similar age range and test–retest interval. The mean overall full-scale IQ of the 20 children during the initial and post-1-year examinations was 106.05 and 113.75, respectively, and showed a statistically significant increase (p < 0.01). Based on the subscale index, the verbal comprehension index (VCI) and processing speed index (PSI) scores both showed a statistically significant increase from 100.6 to 106.75 and from 108.05 to 119.05 (p < 0.01), respectively. The PSI of the children included in the analysis showed a statistically significant increase compared to the historical control group. This study suggests that children who participate in Mahjong classes during their childhood have increased PSI scores of WISC-IV.